Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557047
|View full text |Cite
|
Sign up to set email alerts
|

Bodies in motion

Abstract: Robotic telepresence systems-videoconferencing systems that allow a remote user to drive around in another locationprovide an alternative to video-mediated communications as a way of interacting over distances. These systems, which are seeing increasing use in business and medical settings, are unique in their ability to grant the remote user the ability to maneuver in a distant location. While this mobility promises increased feelings of "being there" for remote users and thus greater support for task collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Telepresence, a term originally coined by Minsky [8], means being present in a remote location through technology.To increase the mobility of the user, it is natural to mount a camera and a screen on a mobile robot, often referred to as a telepresence robot. There is evidence that even this kind of simple telepresence robots increase the feeling of presence, the degree of "being there" often measured in VR research [9], of the remote user over a stationary video call [10]. Research has shown multiple uses for robotic telepresence, such as students who otherwise cannot attend lectures [11], [12], social interaction [13], and telemonitoring on the basis of medical consultation [14].…”
Section: Related Workmentioning
confidence: 99%
“…Telepresence, a term originally coined by Minsky [8], means being present in a remote location through technology.To increase the mobility of the user, it is natural to mount a camera and a screen on a mobile robot, often referred to as a telepresence robot. There is evidence that even this kind of simple telepresence robots increase the feeling of presence, the degree of "being there" often measured in VR research [9], of the remote user over a stationary video call [10]. Research has shown multiple uses for robotic telepresence, such as students who otherwise cannot attend lectures [11], [12], social interaction [13], and telemonitoring on the basis of medical consultation [14].…”
Section: Related Workmentioning
confidence: 99%
“…However, the shortcomings of AR tool may be recognised in work situations that require mobility requiring specificity in visual guidance as part of the remote collaboration. The missing sensation of being there can be simulated by having some sort of control over the stream, referred to as telepresence (Gauglitz, Nuernberger, Turk, & Hollerer, 2014bRae, Mutlu, & Takayama, 2014. Telepresence may enable control of the view within the limits of a selected area guided by the remote person, who can also propose a different viewpoint by directing the camera in the desired location (Jo & Hwang, 2013).…”
Section: Augmented Video Stream With Pointing and Drawingmentioning
confidence: 99%
“…In this thesis, my focus is on designing systems to enable a remote expert assist a worker in the workplace during a physical task. Even here, the range of possible tasks varies from simple, everyday tasks -like cooking or assembling furniture (Rae et. al., 2014) -, to very sensitive tasks like repairing and maintaining a jet engine, or operating the control board in a power plant.…”
Section: Chapter Three: System Design and Implementationmentioning
confidence: 99%